THE EFFECTIVENESS OF SELF-MANAGEMENT INTERVENTIONS IN REHABILITATION FOR POST-STROKE PATIENTS: A SCOPING REVIEW - Hany, Alfrina; Dianinta, Ni Luh Marga; Vatmasari, Ratih Arum (MNJ (Malang Neurology Journal), 2026)
Background: Patients with stroke have great challenges in dealing with their disease, due to long-term disability and even death. Post-stroke self-management can be one approach in the rehabilitation program. Objective: The aim of this review is to identify the effectiveness of self-management interventions in post-stroke patients in carrying out rehabilitation programs. Methods: A scoping review was conducted based on PRISMA guidelines. Four electronic databases (Google Scholar, ScienceDirect, ProQuest, and PubMed) were searched for English-language articles published from 2016 to 2022. The search used combinations of the keywords “self-management,” “rehabilitation,” “post-stroke patients,” “stroke patients,” and “experimental study.” Studies were selected using inclusion and exclusion criteria structured with the PICOS framework, resulting in the identification of 10 eligible experimental studies, including randomized controlled trials and quasi-experimental designs Results: The self-management interventions consistently produced positive outcomes for post-stroke patients. The interventions improved self-efficacy, self-management behaviors, functional abilities, quality of life, treatment adherence, and performance of daily activities. Various strategies such as health empowerment interventions, structured self-management programs, goal-oriented approaches, digital health tools, and virtual reality—demonstrated effectiveness in enhancing patients’ preparedness for community reintegration and reducing complications and rehospitalization. Conclusion: Technology utilization may be considered for the development of appropriate self-management in stroke patients.